Analisis Kesulitan Siswa dalam Pembelajaran Matematika dengan Menggunakan Metode Pembelajaran Make a Match - Yohana Mitra Enjelika Tambunan; Josep Nainggolan; Syahrial Syahrial (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study aims to explore and analyze the challenges students encounter in learning mathematics, particularly in grasping the concepts of cubes and rectangular prisms, through the implementation of the Make a Match learning method. This method was selected due to its potential to enhance students' engagement, participation, and comprehension in the learning process. However, its application still faces several obstacles that hinder effective learning. This research adopts a qualitative approach, utilizing observation, interviews, and diagnostic tests as data collection techniques. The findings indicate that students experience various difficulties, including: (1) differentiating the characteristics of cubes and rectangular prisms, (2) comprehending the concepts and performing calculations related to their volume and surface area, and (3) constructing and accurately illustrating their nets. Several factors contribute to these challenges, such as a lack of fundamental conceptual understanding, difficulty in relating the material to real-life situations, and limitations in spatial visualization skills. The outcomes of this study provide insights for teachers in developing more effective and efficient instructional strategies, including the integration of concrete teaching aids, interactive media, and personalized guidance tailored to students' specific needs. Therefore, optimizing the implementation of the Make a Match method is expected to enhance students' conceptual understanding more effectively.